IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) BIDANG EMPOWERMENT PT. PERTAMINA RU-II DUMAI - Ilhamdi Prayadi Putra; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
As one of the major companies operating in Dumai, PT. Pertamina RU-II is should be care about and take part in improving the welfare of local communities, especially around the company's operations area. To accommodate it, PT. Pertamina RU-II implementing it in the form of CSR programs of empowerment. To achieve the realization of the program company will require input from local authorities and society, so that the programs will be precisely target as it needs. This research aims to determine how’s the planning, implementing, evaluating, and reporting conducted by PT. Pertamina RU-II in implementation of their CSR empowerment programs.This study uses qualitative research with descriptive approach. Research is located in the main office of PT. Pertamina RU-II Dumai located at Jalan Raya Putri Tujuh No. 1 Kota Dumai. This research began on December 2016 and ended on April 2017. There are 3 people who became subjects of this research which is Section Head of Public Relations and CSR Officer’s at PT. Pertamina RU-II. While object of this research is the implementation of CSR programs of empowerment PT. Pertamina RU-II Dumai. The technique of collecting data are using interviews, observation, and documentation. Data analysis technique using descriptive qualitative analysis by Miles and Huberman. Technical data and validity check is using the extension of participation and triangulation.The results of this research shows that public relations of PT. Pertamina RU-II Dumai has perform several stages in implementing their CSR programs of empowerment such as: First, company charted the region area using social mapping trough cooperation with the third parties such as University. Second, in implementing its CSR programs company will cooperated with some partners such as PNPM Mandiri and LPMK. Third, evaluations from the CSR programs that has been done will be conducted by the auditor team from the head office of PT. Pertamina (Persero) located in Jakarta, while the evaluation of the program will be conducted by PT. Pertamina RU-II along with their working partners from the CSR program’s activity. Last, the evaluation results will be reported to the Senior CSR Officer’s at headquarters in Jakarta and then they will be publish it on the Annual Report which is accessible to the entire people in this country. Implementation of the CSR programs always refers to three aspects of the triple bottom line by John Elkington, which is People, Profit and PlanetKeywords: Public Relations, Corporate Social Responsibility, Empowerment